2003
DOI: 10.1111/j.1471-0528.2003.03044.x
|View full text |Cite
|
Sign up to set email alerts
|

Can enquiries into severe acute maternal morbidity act as a surrogate for maternal death enquiries?

Abstract: Objective To assess whether severe acute maternal morbidity (SAMM, 'near misses') can be used as a surrogate of an analysis of maternal deaths to describe the pattern of severe maternal disease and avoidable factors related to it. Design Prospective, descriptive study.Setting A SAMM and maternal mortality audit was conducted in three clearly defined geographical areas, consisting of rural and urban settings in South Africa. Population Indigent black African pregnant women.Method Cases of SAMM and maternal deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 3 publications
2
55
1
8
Order By: Relevance
“…9 As per the causes, both obstetric and non-obstetric, seeking ICU care, it shows that there is no change in common cause of ICU admissions over a last decade. 10 Among early pregnancy complication group, abortion-related hospital admissions predominated. This emphasises the need of monitoring it and quantifying the magnitude of adverse health effects of unsafe abortion in developing countries like India.…”
Section: Discussionmentioning
confidence: 99%
“…9 As per the causes, both obstetric and non-obstetric, seeking ICU care, it shows that there is no change in common cause of ICU admissions over a last decade. 10 Among early pregnancy complication group, abortion-related hospital admissions predominated. This emphasises the need of monitoring it and quantifying the magnitude of adverse health effects of unsafe abortion in developing countries like India.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,30 Because of the resemblance in diagnostic patterns between near-miss at facility level and maternal mortality at regional level, and a reported similarity of substandard care, it has been suggested that severe morbidity can act as a surrogate analysis of maternal deaths. 31 However, the disease profile for near-miss versus maternal mortality differed considerably among the hospitals we studied, leading us to conclude that in similar settings, near-miss may be used advantageously to complement maternal mortality reviews, although it should not replace them.…”
Section: Rö ö St Et Almentioning
confidence: 91%
“…10,11 In these two reports, there was a 50% drop in maternal mortality within a 3pyear intervention period, which is similar to the pattern noted in our study. There are also several studies of facilitypbased audits of perinatal deaths, 20 uterine rupp p ture, 21 nearpmisses [22][23][24] or criterionpbased audit. 25,26 However, controlled evaluation studies of audit interventions are rare and the absolute or relative effects of these approaches on professional practices and outcomes are generally only small to moderate.…”
Section: Special Theme -Estimating Mortalitymentioning
confidence: 99%